EVALUASI KENYAMANAN TERMAL PADA UNIT HUNIAN APARTEMEN MAJESTY - Royana, Vina Agustina (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Parahyangan, 2009)
AbstractÂ Comfort, especially thermal comfort, is one of many aspects that should be available in a housing building. Others are security, accessibility, and health, so the inhabitants will feel at home. In humid tropical climate, high sun radiation and humidityÂ become the major problems. The problems need certain solutions to create thermalÂ comfort.Â Vertical housing (apartment) should have a design that responds to the climate,Â especially the facade design. Building facade willÂ influenceÂ the thermal comfort quality in the building. Moreover, the housing units orientation and the different units height willÂ affect the thermal comfort inside it.Â The Majesty Residence represents the facade problem which doesnt respond to the climate. This apartmentâs shape is letter T, which make various unit orientations. ToÂ respond to the problems, analysis about the thermal comfort linked to the design principles of vertical housing is done. These principles areÂ orientation, building form, unit orientation, construction, material, color, opening, and respond to the sun radiation. FromÂ the analysis, the right material, color, construction, and orientation for humid tropical climate can reduce the climatic problems. Therefore, the comfort zone can be created inside and outside the building.Â Â Key Words: thermal comfort, housing units, Majesty ApartmentÂ AbstrakÂ Kenyamanan khususnya kenyamanan termal merupakan salah satu aspek yang perlu dihadirkan dalam bangunan hunian, selain aspek keamanan, kemudahan, dan kesehatan, agar penghuni merasa betah. Di daerah tropis hangat lembab, radiasi matahari dan kelembaban udara yang tinggi menjadi masalah iklim utama. Masalah tersebut memerlukan pengendalian khusus untuk menciptakan kenyamanan termal.Â Bangunan hunian vertikal (apartemen) sudah selayaknya memiliki desain yang merespon iklim, terutama bagian fasad. Fasad bangunan akan mempengaruhiÂ kualitas kenyamanan termal ruang di dalamnya. Selain itu orientasi unit hunian dan ketinggian unit yang berbeda akan mempengaruhi kenyamanan unit hunian yang berbeda juga.Â Apartemen